Cold peace : Russia's new imperialism - Bugajski, Janusz 1954- (Praeger, 2004)
Near or temporary abroad? -- Russia's foreign policy arsenal -- Retaining a union : Belarus and Kaliningrad -- Regaining a commonwealth : Ukraine and Moldova -- Blocking Western encroachment : the Baltic States -- Neutralizing the core : Central Europe -- Exploiting crises : Adriatic Balkans -- Exporting influence : Black Sea Balkans -- Looking ahead